Calcium-channel number critically influences synaptic strength and plasticity at the active zone - Sheng, Jiansong; Zheng, Hongwei; Kuner, Thomas (Nature neuroscience, 2012)
How synaptic-vesicle release is controlled at the basic release structure, the active zone, is poorly understood. By performing cell-attached current and capacitance recordings predominantly at single active zones in rat calyces, we found that single active zones contained 5-218 (mean, 42) calcium channels and 1-10 (mean, 5) readily releasable vesicles (RRVs) and released 0-5 vesicles during a 2-ms depolarization. Large variation in the number of calcium channels caused wide variation in release strength (measured during a 2-ms depolarization) by regulating the RRV release probability (PRRV) and the RRV number. Consequently, an action potential opened ~1-35 (mean, ~7) channels, resulting in different release probabilities at different active zones. As the number of calcium-channels determined PRRV, it critically influenced whether subsequent release would be facilitated or depressed. Regulating calcium channel density at active zones may thus be a major mechanism to yield synapses with different release properties and plasticity. These findings may explain large differences reported at synapses regarding release strength (release of 0, 1 or multiple vesicles), PRRV, short-term plasticity, calcium transients and the requisite calcium-channel number for triggering release.